Combination of supercritical CO2 and high-power ultrasound for the inactivation of fungal and bacterial spores in lipid emulsions - Angela Gomez-Gomez; Edmundo Brito-de la Fuente; Críspulo Gallegos; Jose V. Garcia-Perez; Jose Benedito (Ultrasonics Sonochemistry, 2021)
For the first time, this study addresses the intensification of supercritical carbon dioxide (SC-CO2) treatments using high-power ultrasound (HPU) for the inactivation of fungal (Aspergillus niger) and bacterial (Clostridium butyricum) spores in oil-in-water emulsions. The inactivation kinetics were analyzed at different pressures (100, 350 and 550 bar) and temperatures (50, 60, 70, 80, 85 °C), depending on the microorganism, and compared to the conventional thermal treatment. The inactivation kinetics were satisfactorily described using the Weibull model.Experimental results showed that SC-CO2 enhanced the inactivation level of both spores when compared to thermal treatments. Bacterial spores (C. butyricum) were found to be more resistant to SC-CO2 + HPU, than fungal (A. niger) ones, as also observed in the thermal and SC-CO2 treatments. The application of HPU intensified the SC-CO2 inactivation of C. butyricum spores, e.g. shortening the total inactivation time from 10 to 3 min at 85 °C. However, HPU did not affect the SC-CO2 inactivation of A. niger spores. The study into the effect of a combined SC-CO2 + HPU treatment has to be necessarily extended to other fungal and bacterial spores, and future studies should elucidate the impact of HPU application on the emulsion’s stability.